Pemberian Layanan Konseling Kelompok Dengan Tehnik Problem Solving Untuk Meningkatkan Pemahaman Karir Siswa Kelas VIIIa SMP Negeri 1 Sikur - Mahyatun, Baiq; Yulianti, Dewi; Miranti, Purna (Universitas Nusantara PGRI Kediri, 2023)
The aim of the research entitled group counseling services with problem solving techniques is to determine students' career understanding. This research methodology uses quantitative methods with the type of research being pre-experimental design, and the research design used is one group pretest and post test. Analysis of the data obtained is t-table (6.002>2.365) at a significance level of 5%, showing that there is an influence to increase career understanding with group counseling services using problem solving techniques for class VIIIA students, so it can be concluded